2013
DOI: 10.1111/mec.12457
|View full text |Cite
|
Sign up to set email alerts
|

MHC class I expression dependent on bacterial infection and parental factors in whitefish embryos (Salmonidae)

Abstract: Ecological conditions can influence not only the expression of a phenotype, but also the heritability of a trait. As such, heritable variation for a trait needs to be studied across environments. We have investigated how pathogen challenge affects the expression of MHC genes in embryos of the lake whitefish Coregonus palaea. In order to experimentally separate paternal (i.e. genetic) from maternal and environmental effects, and determine whether and how stress affects the heritable variation for MHC expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 115 publications
5
31
2
Order By: Relevance
“…This decrease suggests a transition of the egg as substrate for bacteria from unselective to more selective throughout the course of embryonic development. Our field study therefore supports conclusions derived from recent laboratory experiments (Clark and Wedekind 2011;Clark et al 2013Clark et al , 2014. Fig.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This decrease suggests a transition of the egg as substrate for bacteria from unselective to more selective throughout the course of embryonic development. Our field study therefore supports conclusions derived from recent laboratory experiments (Clark and Wedekind 2011;Clark et al 2013Clark et al , 2014. Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Fish embryos seem to complement and specifically increase their immunity through time (Romero and Navarrete 2006). Indeed, towards the end of embryogenesis, important immune genes are expressed (Clark et al 2013) and the immune system can be shown to influence the embryos' resistance to microbial challenges (Ellis 2001;Wedekind et al 2004;Pitcher and Neff 2006). In-vitro fertilized whitefish eggs have been used as models to study genetic and maternal effects during bacterial pathogen incubation (von Siebenthal et al 2009) using full factorial breeding designs ('North Carolina II design', Lynch and Walsh 1998).…”
Section: Time Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…At later developmental stages, the importance of zygotic gene expression becomes crucial for the interaction with associated bacteria (Finn ; Clark et al . , ). Host genetic effects could be revealed for important embryo life‐history traits such as mortality in Oncorhynchus tshawytscha (Aykanat et al .…”
Section: Introductionmentioning
confidence: 99%